RING Zinc Finger Proteins in Plant Abiotic Stress Tolerance - Han, Guoliang; Qiao, Ziqi; Li, Yuxia; Yang, Zongran; Wang, Chengfeng; Zhang, Yuanyuan; Liu, Lili; Wang, Baoshan (Frontiers in Plant Science, 2022)
RING zinc finger proteins have a conserved RING domain, mainly function as E3 ubiquitin ligases, and play important roles in plant growth, development, and the responses to abiotic stresses such as drought, salt, temperature, reactive oxygen species, and heavy metals. RING zinc finger proteins act in abiotic stress responses mainly by modifying and degrading stress-related proteins. Here, we review the latest progress in research on RING zinc finger proteins, including their structural characteristics, classification, subcellular localization, and physiological functions, with an emphasis on abiotic stress tolerance. Under abiotic stress, RING zinc finger proteins on the plasma membrane may function as sensors or abscisic acid (ABA) receptors in abiotic stress signaling; Some RING zinc finger proteins accumulate in the nucleus may act like transcription factors to regulate the expression of downstream abiotic stress marker genes through direct or indirect ways; Most RING zinc finger proteins usually accumulate in the cytoplasm or nucleus and act as E3 ubiquitin ligases in the abiotic stress response through ABA, mitogen-activated protein kinase (MAPK), and ethylene signaling pathways. We also highlight areas where further research on RING zinc finger proteins in plants is needed.